The architecture and ppGpp-dependent expression of the primary transcriptome of Salmonella Typhimurium during invasion gene expression. - Ramachandran, V; Shearer, N; Jacob, J; Sharma, C; Thompson, A (BioMed Central, 2012)
BACKGROUND: Invasion of intestinal epithelial cells by Salmonella enterica serovar Typhimurium (S. Typhimurium) requires expression of the extracellular virulence gene expression programme (ST(EX)), activation of which is dependent on the signalling molecule guanosine tetraphosphate (ppGpp). Recently, next-generation transcriptomics (RNA-seq) has revealed the unexpected complexity of bacterial transcriptomes and in this report we use differential RNA sequencing (dRNA-seq) to define the high-resolution transcriptomic architecture of wild-type S. Typhimurium and a ppGpp null strain under growth conditions which model ST(EX). In doing so we show that ppGpp plays a much wider role in regulating the S. Typhimurium ST(EX) primary transcriptome than previously recognised. RESULTS: Here we report the precise mapping of transcriptional start sites (TSSs) for 78% of the S. Typhimurium open reading frames (ORFs). The TSS mapping enabled a genome-wide promoter analysis resulting in the prediction of 169 alternative sigma factor binding sites, and the prediction of the structure of 625 operons. We also report the discovery of 55 new candidate small RNAs (sRNAs) and 302 candidate antisense RNAs (asRNAs). We discovered 32 ppGpp-dependent alternative TSSs and determined the extent and level of ppGpp-dependent coding and non-coding transcription. We found that 34% and 20% of coding and non-coding RNA transcription respectively was ppGpp-dependent under these growth conditions, adding a further dimension to the role of this remarkable small regulatory molecule in enabling rapid adaptation to the infective environment. CONCLUSIONS: The transcriptional architecture of S. Typhimurium and finer definition of the key role ppGpp plays in regulating Salmonella coding and non-coding transcription should promote the understanding of gene regulation in this important food borne pathogen and act as a resource for future research.